ALL CITIES ARE DIFFERENT: Moving creative workforce research forward to a new specificity - Bennett, Dawn; Fitzgerald, Scott; Rainnie, Al (State of Australian Cities Conference 2011, 2011)
The cultural sector and its workforce are often positioned as economic drivers, and important themes within this discourse have included relationships between the cultural sector and human capital, urban regeneration, community engagement, branding, and image. Little of the research underpinning these arguments has documented the work practices, orientations, attitudes, career trajectories and skill requirements of individual creative workers, and even less has considered the spatially specific nature of labour conditions and career trajectories to produce a differentiated analysis of work and career. What happens within any locality over time will partially result from the changing roles it plays within the broader spatial divisions of labour within which it is emplaced. However, we argue that it is insufficient to claim that all cities are different; rather, there is a need to examine the specificity of work in each location.In this paper, the second in a series that examine specific elements of creative work, we consider spatiality with specific reference to the use of networks. Drawing on a case study of the film and television industries in Perth we raise the possibility of approaching such research by combining the global production network approach, labour process analysis, and research that looks within individual practice.